Culture Shock Mahasiswa Indonesia dalam Studi di Luar Negeri - Adinda Annisa Zahra; Tia Muthiah Umar (UNISBA Press, 2024)
Abstract. As we already know, Culture Shock is something that can be said to be a habit when going through a process of cultural adaptation to a new environment, one of which is abroad. In accordance with the research that I will research, it is entitled